Phenolic compounds, biological activities and trace elements of Capparis ovata var. canescens - EMRE, GİZEM; ÇAM, MUHAMMET EMİN; TAŞKIN, TURGUT (My University, 2020)
Introduction: Capparis species (Capparaceae), also called caper, grow naturally in various regions of the world. Caper is a plant with medicinal and aromatic properties. Flower buds, root bark, and fruits of the plant are used in folk medicine due to their analgesic, wound healing, cell regeneration, tonic, and diuretic effects. Objective: The aim of this research was to evaluate in vitro (anti-urease, antioxidant, anticholinesterase) and in vivo (anti-inflammatory) biological activities of caper (C. ovata var. canescens). In addition, we aimed to identify its major phenolic compounds using high performance liquid chromatography with a photodiode array detector (HPLC-DAD) and confirmate them using quadrupole time-of-flight liquid chromatography with tandem mass spectrometry (Q-TOF-LC/MS). Also, we quantified the concentrations of several trace and major elements in plant samples using inductively coupled plasma-mass spectrometry (ICP-MS). Methods: The antioxidant, anti-urease and anticholinesterase activities of different plant extracts were evaluated using DPPH, FRAP, ABTS/TEAC, Indophenol and Ellman tests. The identification of phenolic compounds and trace element contents was performed using HPLC and Q-TOF-LC/MS and ICP-MS. Results: Soxhlet methanol extract exhibited the strongest anti-urease, antioxidant (ABTS/TEAC) and anticholinesterase activity. Soxhlet and maceration methanol extracts demonstrated significant anti-inflammatory effect in the altered edema size after the second hour of carrageenan injection. The active phenolic compounds in Soxhlet methanol extract were identified as rutin, quercetin-hexoside-hexoside, quercetin-3-O-hexoside and kaempferol-3-O-rutinoside. In addition, the average concentrations of vanadium, chromium, manganese, cobalt, copper, nickel, arsenic, selenium, zinc and lead were within the permissible limits defined by WHO for medicinal plants. However, it was found that the concentrations of cadmium and iron were higher than the maximum permissible limits. Conclusion: Our results suggest that although caper has a strong biological activity, it should be consumed carefully due to the excess amount of cadmium and iron elements it contains.